The self-esteem of the it manager as the basis for the success of the organization - Pidbutska, N. V.; Knysh, A. Ye.; Chebakova, Yu. H. (My University, 2020)
The aim of the publication was to clarify the connection between the level of self-esteem of the IT-manager and the success of the organization he heads. As indicators of the success of the organization were considered: 1) profit growth; 2) the number of projects completed during the year; 3) staff turnover; 4) employee satisfaction with work. The study involved 18 managers who represented 8 Ukrainian IT companies. Study has shown that self-esteem of manager affects not only his professional success, but also success of the organization. There are statistically significant differences in the level of self-esteem of IT managers representing companies with different levels of success. The most successful are those companies run by managers with average level of self-esteem.

Цель реферата заключалась в уточнении связи между уровнем самооценки IT-менеджера и успешностью организации, которой он руководит. В качестве показателей успешности организации рассматривались: 1) рост прибыли; 2) количество реализованных за год проектов; 3) текучесть кадров; 4) удовлетворенность сотрудников работой. В исследовании приняли участие 18 менеджеров, которые представляли 8 украинских IT-компаний. Исследование показало, что самооценка менеджера влияет не только на его профессиональную успешность, но и на успешность организации в которой он работает. Существуют статистически значимые различия в уровне самооценки IT-менеджеров, представляющих компании с разным уровнем успешности. Наиболее успешными являются те компании, которыми управляют менеджеры со средним уровнем самооценки.
Keywords: managers; self-esteem; organizational success; human resources; менеджеры; самооценка; успешность организации; кадровый потенциал